Study of the behavior of an acid-enhanced electrokinetic remediation performed with a real soil spiked with lead - Nekrasova, Marina; Sidorenko, Sergey; Galkin, K.A.; Pisar, L.U.; García-Herruzo, Francisco; Rodríguez-Maroto, José Miguel; Gómez-Lahoz, César; Vereda-Alonso, Carlos; Villén-Guzmán, María Dolores (Northeastern University, 2013)
Since the 1980s decade there has been a sharp increase in the research for the development of new techniques for the remediation of contaminates sites, because one after another country realized that the economic budget that would require the recovery of all these sites is simply unaffordable. Most countries have developed criteria to prioritize the remediation of those sites that were bearing the most severe risks for humans or the environment. Also an important effort has been done in order to make available new techniques more economic. Regarding both, the risk assessment and the development of new techniques, the most typical research approaches at the lab-scale are either the use of an already contaminated soil or the use of a model soil in which the contaminant is spiked. In the first case, the complexity of the soil matrix makes the derivation of conclusions applicable to other soils quite difficult. In the second case, the simplicity of the soil matrix can make the results more reproducible at different labs, but may be also of limited interest for the real contaminated soils, since that simplicity will be found in very few real cases. Furthermore, the contact time between the contaminants and the real contaminated soils is usually larger than several months and can even be in the order of centuries. Obviously this contact time may not be used in the experiments at the lab scale. In these cases, typically, in the most favorable case, a series of experiments of different contact time are carried out, which range from some minutes or few hours to several days or even weeks. Then a comparison is made from which the conclusion is usually that a contact time of several hours or few days is large enough to assure that the different equilibria are reached. Nevertheless, it is also widely known that the transport of contaminants through the soil matrix can be very slow. Also that it can be difficult to distinguish between the pseudo-steady states that can control the partitioning between different soil compartments and the real thermodynamic partitioning. Thus, there is a clear lack of experimental results obtained for soils that are spiked with a certain contaminant and allowed a variable contact time (ageing) ranging from weeks to years. In this work we present the first results that we have obtained for a soil that presents a moderate background concentration of lead, and was spiked with an additional amount of lead nitrate. The mobility of lead is studied by the BCR sequential extraction procedure, which divides the lead concentration into three fractions (weak acid soluble, reducible and oxidizable), besides the residual fraction that is obtained to investigate the mass balance, and support the quality of the analysis. It has been shown in the literature that the BCR fractionation can be used, together with mathematical models, to do reliable predictions about the maximum removal yield that can be obtained from several remediation techniques, including the electrokinetic remediation. In this paper we present the results of an early stage of the ageing process. The electrokinetic experiment is performed in a duplicated lab column assay using a constant current density and the disposition of the two columns electrically in series, to allow the maximum reproducibility of the results.
12th International Symposium on Electrokinetic Remediation, EREM2013
Keywords: Contaminación; Restauración ecológica; Electrokinetic remediation; Heavy metals